2012
DOI: 10.1117/1.oe.52.2.021010
|View full text |Cite
|
Sign up to set email alerts
|

Review of alkali laser research and development

Abstract: Abstract. In this review we present an analysis of optically pumped alkali laser research and development from the first proposal in 1958 by Schawlow and Townes to the current state. In spite of the long history, real interest in alkali vapor lasers has appeared in the past decade, after the demonstration of really efficient lasing in Rb and Cs vapors in 2003 and the first successful power scaling experiments. This interest was stimulated by the possibility of using efficient diode lasers for optical pumping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…As the medium of a DPAL is in gas-state, the thermally-induced effect for high-powered operations should be lower than the most conventional DPSSL systems [9][10][11]. However, if the output of a DPAL is up to several kilowatts, the thermally-induced effect cannot be simply ignored [12,13].…”
Section: Introductionmentioning
confidence: 96%
“…As the medium of a DPAL is in gas-state, the thermally-induced effect for high-powered operations should be lower than the most conventional DPSSL systems [9][10][11]. However, if the output of a DPAL is up to several kilowatts, the thermally-induced effect cannot be simply ignored [12,13].…”
Section: Introductionmentioning
confidence: 96%
“…Both the theoretical and the experimental studies have proved that a DPAL is now becoming one of the most promising candidates to realize an output with both good beam quality and high power [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies have addressed only output performances. Although a few studies have been reported in regarding the characteristics of DPALs in time domain, the detailed analyses of relaxation oscillation (RO) generation still keep infrequent at present [18][19][20][21]. RO is a phenomenon that involves energy exchanges in the time domain between population inversion and cavity photons for optical oscillation [22].…”
Section: Introductionmentioning
confidence: 99%